Response to Treatment in IgG4-Related Disease Assessed by Quantitative PET/CT Scan. (June 2021) - Orozco-Gálvez, Olimpia; Fernández-Codina, Andreu; Simó-Perdigo, Marc; Pinal-Fernández, Iago; Martínez-Valle, Fernando
Abstract : Objective: The aim of this study was to assess disease activity by different PET/CT measurements in IgG4-related disease (IgG4-RD) flares and their correlation with the IgG4-RD responder index (IgG4-RI). Patients and Methods: Patients were retrospectively recruited from a single center in Barcelona, Spain. They all had IgG4-RD flares with an 18 F-FDG PET/CT examination performed within the 2 first weeks of the flare onset and another one after at least 3 months of treatment between 2012 and 2018. Epidemiologic, clinical, laboratory, and therapeutic data were collected at baseline and at follow-up. Semiquantitative and volumetric measurements from PET/CT explorations were recorded. In addition, a 5-point visual scale was (adapted Deauville score) trialed. The IgG4-RI was used as the criterion standard to assess response before and after treatment. Results: Eighteen patients with a total of 23 flares were included. The median time to second PET/CT examination was 7 months. Remission (complete and partial) according to IgG4-RI was observed in 20 flares (87%). All PET/CT measurements (SUVmax and SUVmean, total lesion glycolysis, MTV, and adapted Deauville score) were statistically significantly lower on the follow-up evaluation, except for the size of the lesion. The correlation of all these parameters with the IgG4-RI was positive except for SUVmean and the size of the lesion. Conclusions: Semiquantitative, volumetric, and visual parameters in PET/CT scans correlated with response to treatment assessed by IgG4-RI. Volumetric and visual items are less subject to variations and could be used to improve activity scores and treatment strategies.